Build Your Money Muscles: Nine Simple Exercises for Improving Your Relationship with Money - Angela C Collins (Journal of Financial Therapy, 2012)
In her book, "Build Your Money Muscles: Nine Simple Exercises for Improving Your Relationship with Money", Joan Sotkin outlines a step-by-step process of how to identify, interpret, and repair relationships with money. This book focuses more on the thoughts, beliefs, and emotions (referred to as TBE) around money than actual money management skills. These thoughts, beliefs, and emotions create behaviors which ultimately construct financial situations for better or worse.
Keywords: financial therapy